Professional Legal Consciousness: An Ideal Theoretical Model or Legal Reality? - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2024)
The article analyzes and evaluates the type of legal consciousness, which in the domestic literature has been defined and is still defined as professional legal consciousness, which, according to the author, must meet the following requirements: it is enough to know the current legislation applied in practice, respectful attitude to law and how consequence, the ability to apply the law, making effective and legal decisions. Emphasizing that it would be illogical to reduce into one type of carriers of professional legal consciousness those officials who carry out their professional activities on the basis of the law, respecting the law, and those law enforcers who commit offenses and even crimes, while showing a negative attitude towards the law, the position is substantiated, according to which the analyzed type of legal consciousness is considered as an ideal theoretical model and defined as practical legal consciousness.